2005
DOI: 10.1113/jphysiol.2005.082701
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal cocaine exposure increases heart susceptibility to ischaemia–reperfusion injury in adult male but not female rats

Abstract: The present study tested the hypothesis that prenatal cocaine exposure differentially regulates heart susceptibility to ischaemia-reperfusion (I/R) injury in adult offspring male and female rats. Pregnant rats were administered intraperitoneally either saline or cocaine (15 mg kg −1 ) twice daily from day 15 to day 21 of gestational age. There were no differences in maternal weight gain and birth weight between the two groups. Hearts were isolated from 2-month-old male and female offspring and were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
57
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 56 publications
11
57
1
Order By: Relevance
“…Fetal cocaine exposure causes myocardial cell apoptosis, resulting in a decreased number of myocardiocytes at birth and increases the heart's sensitivity to ischemia and reperfusion injury in adult male offspring in a sex-dependent manner (2,4). These studies also showed a correlation between a decrease in both total and phosphorylated protein kinase Cε and increased myocardial sensitivity to ischemia in adult male offspring after fetal cocaine exposure (2).…”
supporting
confidence: 58%
See 4 more Smart Citations
“…Fetal cocaine exposure causes myocardial cell apoptosis, resulting in a decreased number of myocardiocytes at birth and increases the heart's sensitivity to ischemia and reperfusion injury in adult male offspring in a sex-dependent manner (2,4). These studies also showed a correlation between a decrease in both total and phosphorylated protein kinase Cε and increased myocardial sensitivity to ischemia in adult male offspring after fetal cocaine exposure (2).…”
supporting
confidence: 58%
“…Time-dated pregnant SpragueDawley rats were purchased from Charles River Laboratories (Portage, MI). As described previously, the animals were randomly divided into two groups: 1) saline control, and 2) 15 mg/kg cocaine administered intraperitoneally twice daily at 10:00 AM and 4:00 PM from day 15 to 21 of gestational age, the dose that produces plasma cocaine levels in the range of those reported in human cocaine users (2). The animals were allowed to give birth naturally, and no fetal loss in the control and cocaine-treated groups was observed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations